TPR: activities to promote listening in an efl children classroom - Ortega, Verónica; Peña, Jéssica
This monograph is a short investigation of TPR (Total Physical Response) as an important method to develop the listening skill in children. Our main goal is to find out the best way to help children to use this foreign language, which is English, as they use their mother tongue in their lives, without any complication and in a funny way in order to make them feel involve in their learning process, without too much stress. Moreover, we want to share these ideas with facilitators of English because we, as English teachers, know that it is helpful to have some different activities in the classroom which provide students a very good way to learn English. Also, this investigation will help teachers to realize that children learn if they feel motivated to learn. This project contains some good activities which are based on TPR, such as: Storytelling, Strip Story and Chants. These techniques of TPR help children to develop listening skill in their lives. Moreover, TPR helps teachers as well as students to increase vocabulary in a different way without stress and pressure. Also, they learn in an active way, using their bodies to do commands with the teacher; not only listening to the teacher. In this case, TPR helps to develop children´s listening in their short age. In the future they will be able to speak without any problem.